2012
DOI: 10.1186/1477-7525-10-30
|View full text |Cite
|
Sign up to set email alerts
|

Impact of self-rated osteoarthritis severity in an employed population: Cross-sectional analysis of data from the national health and wellness survey

Abstract: BackgroundAlthough osteoarthritis (OA) often affects older persons, it has a profound effect on individuals actively employed. Despite reports of reduced productivity among workers with OA, data are limited regarding the impact of OA among workers. The objective of this study was to evaluate the impact of self-rated OA severity on quality of life, healthcare resource utilization, productivity and costs in an employed population relative to employed individuals without OA.MethodsThis cross-sectional analysis us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 35 publications
(48 reference statements)
9
76
0
4
Order By: Relevance
“…Four studies focused on knee or hip OA only, [1,15,27,28] while the rest included all types of OA. The sample size of the studies ranged from 1021 [29] to over 1.1 million [16], with eight studies using a non-OA group as a comparator (one reported HRQoL only) [11,14,18,25,[30][31][32][33]. Of the 12 studies reporting direct costs only, 10 were based on claims databases [15-19, 21, 22, 25-27], one on survey data [32], and one on a hospital database [12].…”
Section: Review Resultsmentioning
confidence: 99%
“…Four studies focused on knee or hip OA only, [1,15,27,28] while the rest included all types of OA. The sample size of the studies ranged from 1021 [29] to over 1.1 million [16], with eight studies using a non-OA group as a comparator (one reported HRQoL only) [11,14,18,25,[30][31][32][33]. Of the 12 studies reporting direct costs only, 10 were based on claims databases [15-19, 21, 22, 25-27], one on survey data [32], and one on a hospital database [12].…”
Section: Review Resultsmentioning
confidence: 99%
“…O Os instrumentos utilizados e a análise de dados prevista são descritos a seguir e a discussão foi orientada pela literatura especializada [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][22][23][24][25][26][27][28][29][30][31][32][33] .…”
Section: Metodologiaunclassified
“…Doenças crônicas como câncer, distúrbios osteomusculares, artrite, doenças cardíacas ou neurológicas representam um importante problema de saúde pú-blica, ocasionando limitações funcionais e biopsicossociais, absenteísmo, afastamento das atividades de trabalho e reduzindo os índices de qualidade de vida [1][2][3][4][5] . Atualmente, cerca de 12% das mortes registradas no mundo são relacionadas ao câncer, representando cerca de sete milhões de pessoas.…”
Section: Introductionunclassified
“…5,6 The disease affects the ageing population worldwide 7,8 leading to a high socio-economic burden 9 with substantial financial consequences. 10,11 In a healthy condition, the lubricants present in the synovial fluid, such as Hyaluronic acid (HA), lubricin 12 and the surface-active phospholipids (SAPL) 13,14 act as shock absorbers protecting the joint against compressive damage.…”
Section: Introductionmentioning
confidence: 99%